2022
DOI: 10.2147/cmar.s351791
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nivolumab in the Management of First-Line Unresectable Advanced or Recurrent Gastric Cancer in Combination with Chemotherapy: Lessons from the Japanese Experience

Abstract: Recently, immune checkpoint inhibitor (ICI), such as anti-programmed cell death-1 (PD-1) or programmed cell death ligand-1 (PD-L1) monoclonal antibodies, has provided clinical benefits in various cancer types including advanced gastric cancer (AGC). Nivolumab, a monoclonal anti-PD-1 antibody, firstly showed an improvement in the overall survival (OS) in patients with AGC in the ATTRACTION-2 trial. Recently, chemotherapy plus nivolumab, as a first-line treatment for AGC, showed both OS and progression-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the AVAGAST trial conducted more than a decade ago, the frequency of patients who received chemotherapy after disease progression varied widely, similar to these four recent clinical trials (64–68% in the Asian trial vs. 33–54% in the global trial) [ 38 ]. Moreover, 14% of patients in the KEYNOTE-062 trial and 9% of patients in the Checkmate 649 trial received immunotherapy in the control arm, whereas 27% of patients in the ATTRACTION-4 trial received immunotherapy [ 39 ]. These differences in primary sites, multiple lines of treatment, and tumor volume at diagnosis, as well as the widespread use of gastrointestinal endoscopy in Asian counties, may contribute to the longer prognosis of Asian patients.…”
Section: Anti-pd-1/pd-l1 Antibodies Plus Chemotherapy As First-line T...mentioning
confidence: 99%
“…In the AVAGAST trial conducted more than a decade ago, the frequency of patients who received chemotherapy after disease progression varied widely, similar to these four recent clinical trials (64–68% in the Asian trial vs. 33–54% in the global trial) [ 38 ]. Moreover, 14% of patients in the KEYNOTE-062 trial and 9% of patients in the Checkmate 649 trial received immunotherapy in the control arm, whereas 27% of patients in the ATTRACTION-4 trial received immunotherapy [ 39 ]. These differences in primary sites, multiple lines of treatment, and tumor volume at diagnosis, as well as the widespread use of gastrointestinal endoscopy in Asian counties, may contribute to the longer prognosis of Asian patients.…”
Section: Anti-pd-1/pd-l1 Antibodies Plus Chemotherapy As First-line T...mentioning
confidence: 99%
“…Among these, the CheckMate-649 trial demonstrated the efficacy of nivolumab (a PD-1 binding immune checkpoint inhibitor) in combination with chemotherapy as a first-line treatment for human epidermal growth factor receptor 2 (HER2)–negative advanced or metastatic GC [ 3 ]. Currently, nivolumab plus chemotherapy is the standard first-line treatment for advanced or metastatic GC [ 3 , 9 , 11 ].…”
mentioning
confidence: 99%
“…Additional results showed significant improvement in overall survival and progression-free survival in patients with PD-L1 CPS ≥1 and all randomly assigned patients [ 3 ]. However, approval and recommendations for nivolumab differ according to the country or approval agency [ 11 ]. In Korea, nivolumab reimbursement for GC treatment is restricted to patients with PD-L1 CPS ≥5.…”
mentioning
confidence: 99%